Polarimetric Multifrequency and Multi‐incidence SAR Sensors Analysis for Archaeological Purposes. Issue 2 (6th May 2013) - Patruno, Jolanda; Dore, Nicole; Crespi, Mattia; Pottier, Eric; Lasaponara, Rosa; Masini, Nicola
ABSTRACT The aim of the present work was to compare Advanced Land Observing Satellite (ALOS) Phased Array type L‐band Synthetic Aperture Radar (PALSAR) with RADARSAT‐2 C‐band satellite in order to identify the most suitable method for the detection of ground anomalies due to the presence of shallow underground archaeological structures. This comparison was performed over two UNESCO archaeological sites: Djebel Barkal (northern province of Meroe, Sudan) and Samarra (130 km north of Bagdad, Iraq). The choice of these two cultural sites was motivated by their position in a desert area (especially the Djebel Barkal site) where soil moisture has smaller impact on radar wave penetration, thus not compromising data interpretation. The largest difference between the satellites is the spatial resolution, around 20 m for the PALSAR sensor and 9 m for the RADARSAT‐2 satellite. Given the importance of spatial resolution for archaeological purposes, that difference is balanced by the wave band utilized, which can be translated in differences in soil penetration. However, the quite superficial remains in both the sites give different but complementary responses. Polarimetric SAR data were analysed with PolSARpro software, and all the products were then compared with archaeological maps and available optical satellite images, used as a basis for the georeferencing process. This work constitutes a fundamental step in archaeological research toward a correct interpretation of all the scattering mechanisms above or around ancient structures. Additional information, such as meteorological conditions where available and archaeological maps (that can be consulted from the UNESCO website), was used as a support for interpretation of the archaeological areas; in the case of the Iraqi city of Samarra and of the archaeological area of Gebel Barkal, ground‐truth surveys in situ are not allowed for political reasons. Copyright © 2013 John Wiley & Sons, Ltd.